Readings in the Jordanian Arabic dialectology - Loae Fakhri Jdetawy (Technium Social Sciences Journal, 2020)
This research paper discusses Jordanian Arabic dialectology from a sociolinguistic perspective. It limits itself to ‘traditional Arabic dialectology’ (TAD) which deals with the geographical variation of the Arabic dialects. It also aims to uncover the dialectal boundaries of variation of the dialects in the Jordanian Arabic through investigating their geographical distribution in order to reveal any phenomena that are not attested. The findings of the current research paper concluded that due to several influential factors; including social stratification and geographical factors, today the original Jordanian dialects struggle to survive. In addition, the Jordanian chain of dialects witness a case of dialect continuum. The geographical range is marked by extreme dialectal differences between the main dialects in Jordan which results in some breaks in intelligibility between the geographically adjacent Jordanian dialects along the continuum. It was also found that the Jordanian Arabic is characterized by a certain type of diglossia -beyond the standard taxonomy of diglossia- which is called the ‘diglossic code-switching’. In the revealed diglossic situation, different ‘high’ and ‘low’ Jordanian local colloquial varieties (without broaching the Classical Arabic) are used by the Jordanians under different conditions for different functions. Additionally, the original Jordanian local colloquial varieties, i.e., urban, rural, and bedouin dialects and registers are in an ongoing process of daily contact. This contact has increased dramatically in the Jordanian community due to urbanization and the Palestinians’ migration to Jordan. As a result, a dominant urban dialect was emerged and started to be spoken in the Jordanian urban areas nowadays. This newly emerging urban dialect (also called ‘Hybrid variety’ or ‘Modern Jordanian’) consists of a mixture of the original Jordanian urban dialect and the Palestinian urban dialect that is originally descended from Palestine, has started to have considerable influence over the original Jordanian localized dialects in the past few decades in a sense that it has started to have a wider socio-spatial currency and thus became more widely adopted in most of the Jordanian urban areas at the expense of the original Jordanian local colloquial varieties which eventually led to force Jordanians to codeswitch between their native dialectal mother tongues and this dominant urban dialect for social motivated purposes. Such practice of adapting a variety of speech is called ‘style shifting’ and such influence was caused by the process of regional dialect levelling.